2015
DOI: 10.1007/s10853-015-9240-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical alloying and thermal analysis of Ta–Ti alloys

Abstract: Tantalum-titanium alloys have widespread potential in biomedical applications due to their superior biocompatibility, favorable mechanical properties, high corrosion resistance, and ability to exhibit shape memory behavior. However, this system is plagued by processing difficulties due to significant differences in melting temperatures, specific weights, and vapor pressures of Ta and Ti. In the present study, mechanical alloying (MA) using high-energy ball milling of Ti-xTa (where x = 50, 60, 70, and 85 wt%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Lisco et al [7] reported the Cadmium Sulphide (CdS) thin films were deposited by two different processes, chemical bath deposition (CBD), and pulsed DC magnetron sputtering (PDCMS) on fluorine doped-tin oxide coated glass to assess the potential advantages of the pulsed DC magnetron sputtering process. Barzilai et al [1] reported the effects of ammonium sulfate on the CdS film produced by CBD using cadmium sulfate as the cadmium source. The concentration of ammonium sulfate was varied from 0 M up to 0.006 M.…”
Section: Introductionmentioning
confidence: 99%
“…Lisco et al [7] reported the Cadmium Sulphide (CdS) thin films were deposited by two different processes, chemical bath deposition (CBD), and pulsed DC magnetron sputtering (PDCMS) on fluorine doped-tin oxide coated glass to assess the potential advantages of the pulsed DC magnetron sputtering process. Barzilai et al [1] reported the effects of ammonium sulfate on the CdS film produced by CBD using cadmium sulfate as the cadmium source. The concentration of ammonium sulfate was varied from 0 M up to 0.006 M.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Transition metals such as V, Nb, and Ta have been widely used to fabricate Ti alloys because of their stability and ease of incorporation into the Ti lattice. 17−19 Among these candidates, Ta emerges as a valuable option for its properties such as the capability of enhancing corrosion resistance 20,21 and its effect on reduction of the TiO 2 band gap. 19,22 Although commercial Ti−Ta alloys, typically fabricated by arc melting, are commercially available, limited control over the chemical or microstructural properties is provided, warranting further thermal or chemical treatments to achieve the desired properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The major challenge limiting the TiO 2 catalytic activity is its band gap because UV-light irradiation is required to trigger electron–hole generation in the semiconductor. , A promising way to modify the optical properties and shift the light activation consists of doping the TiO 2 lattice with a foreign atom, such as a nonmetal element or a transition metal. , Commercial Ti alloys can represent a valid option because of the preexisting microstructure containing one or more foreign doping elements, avoiding expensive, time-consuming post-treatment chemistry. , Transition metals such as V, Nb, and Ta have been widely used to fabricate Ti alloys because of their stability and ease of incorporation into the Ti lattice. Among these candidates, Ta emerges as a valuable option for its properties such as the capability of enhancing corrosion resistance , and its effect on reduction of the TiO 2 band gap. , Although commercial Ti–Ta alloys, typically fabricated by arc melting, are commercially available, limited control over the chemical or microstructural properties is provided, warranting further thermal or chemical treatments to achieve the desired properties . Conversely, fabrication routes such as physical vapor deposition (PVD) sputtering can offer a flexible and versatile solution to creating a customized alloy with controlled surface morphology and chemical composition. PVD sputtering has been beneficial to the fabrication of thin films with enhanced electronic and optical properties; nevertheless, no reports are available on PVD sputtering of Ti alloy to investigate the properties of TiNTs upon electrochemical anodization.…”
Section: Introductionmentioning
confidence: 99%